english Representasi Sinematik Interior Arsitektur Jengki dalam Film Tiga Dara (1956): Representasi Sinematik Interior Arsitektur Jengki dalam Film Tiga Dara (1956) - Ahmad Fajar Ariyanto; Sri Wastiwi Setiawati; Zaqia Ramallah; St. Andre Triadiputra (International Journal of Multidisciplinary Research and Literature, 2026)
Jengki architecture is a distinctive manifestation of Indonesian modernism that emerged in the 1950s, shaped by the post-independence spirit and a deliberate rejection of colonial aesthetic dominance. In the same period, Indonesian cinema developed as a visual medium capable of recording social change, cultural transformation, and shifting urban lifestyles. This study investigates the representation of Jengki architectural interiors in Tiga Dara (1956), directed by Usmar Ismail, using a cinematic approach and Roland Barthes’ semiotic analysis. Employing a qualitative descriptive method, the research draws on literature review, frame-by-frame visual observation, and documentation of film scenes featuring interior spaces. The analysis identifies denotative and connotative meanings of interior elements, including spatial layout, architectural components, lighting, ventilation, furniture, and furnishings as part of the film’s mise-en-scène. The findings reveal that Jengki interiors are represented through asymmetrical spatial compositions, flexible layouts, slanted forms, climatic responsiveness, and hybrid furniture influenced by international modernism. At the connotative level, these visual representations articulate ideas of modernity, freedom, innovation, and national optimism in the construction of post-independence identity. This study highlights the role of film as a valuable visual archive for understanding the development of interior design and architectural discourse in Indonesia’s transition toward national modernity.